Does Capital Structure's Effect and Accounting Conservatism on Business Performance Mediated by Corporate Governance - Suhartono, Edy; Anggapratama, Reza; Junea, Amelia Ivoka (JEM17: Jurnal Ekonomi Manajemen, 2025)
Financial performance is a crucial sign of a business's health that affects its stability and long-term viability. Good corporate governance is essential for transparent decision-making, preventing abuse, and maintaining investor and stakeholder trust. This study identifies a research gap related to The impact of the capital structure and accounting conservatism on financial performance, in relation to corporate governance acting as a moderator, especially in the transportation and logistics sector. Further research is needed to consider additional variables and more complex analysis methods. Using a quantitative approach and panel data analysis, this study examines how Between 2020 and 2022, the financial performance of Indonesian logistics and transportation enterprises is influenced by corporate governance, capital structure, and accounting conservatism. This investigation showed that Conservatism in accounting has no substantial effect on financial results. However, capital structure had a major adverse effect. (coefficient -0.58, P = 0.26; coefficient 0.03, P = 0.587). Despite the favorable effect of corporate governance (coefficient 0.281, P = 0.29), the results were not significant. This research is limited to the transportation and logistics sector, suggesting further exploration in other sectors and considering external factors that influence financial performance. Keywords: The transportation sector, corporate governance, financial performance, Conservatism in accounting and capital structure